Horizon - Kamelia Umirah Kamsani (2015)
This report serves as a documentation of the process in creating the 3-D animated film: Horizon. The report covers through the various stages of animation creation; from story/concept, visual development, production and post-production. Process images are also included in the report for better clarity and understanding.